2020
DOI: 10.1038/s41467-020-19063-7
|View full text |Cite
|
Sign up to set email alerts
|

Siah2 integrates mitogenic and extracellular matrix signals linking neuronal progenitor ciliogenesis with germinal zone occupancy

Abstract: Evidence is lacking as to how developing neurons integrate mitogenic signals with microenvironment cues to control proliferation and differentiation. We determine that the Siah2 E3 ubiquitin ligase functions in a coincidence detection circuit linking responses to the Shh mitogen and the extracellular matrix to control cerebellar granule neurons (CGN) GZ occupancy. We show that Shh signaling maintains Siah2 expression in CGN progenitors (GNPs) in a Ras/Mapk-dependent manner. Siah2 supports ciliogenesis in a fee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 81 publications
3
25
0
Order By: Relevance
“…As development progresses, the number of ciliated cells in the EGL and later also IGL, increases (Figure 4B-D). We noticed that at neonatal stages, ciliated CGNPs were more abundant towards the outer EGL in agreement with earlier studies [45,46]. However, ciliated CGNPs were most frequent in the IGL, and these cilia were also significantly longer (Figure 4B-D).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As development progresses, the number of ciliated cells in the EGL and later also IGL, increases (Figure 4B-D). We noticed that at neonatal stages, ciliated CGNPs were more abundant towards the outer EGL in agreement with earlier studies [45,46]. However, ciliated CGNPs were most frequent in the IGL, and these cilia were also significantly longer (Figure 4B-D).…”
Section: Resultssupporting
confidence: 92%
“…In particular, we found that primary cilium expression was low across young CGNPs and patients, which was somewhat unexpected given the importance of primary cilia for Shh pathway activity [37][38][39][40][41][42][43][44][45][46]. In line, early embryonic CGNPs displayed a partial unresponsiveness to Smo-mediated (i.e., upstream) pathway stimulation, preventing increased proliferation.…”
Section: Introductionmentioning
confidence: 74%
“…GNPs have been shown definitively to be the cell type of origin for Shh-class medulloblastomas ( Goodrich et al, 1997 ; Kim et al, 2003 ; Oliver et al, 2005 ; Rohatgi et al, 2007 ; Yang et al, 2008 ). These tumors express elevated levels of Zeb1 and Siah2 and low levels of Pard complex ( Singh et al, 2016 ; Ong et al, 2020 ), consistent with the polarity trajectories described for mouse GNPs. Genetic deletion of the Patched1 Shh receptor, which stimulates Shh medulloblastoma formation in humans, creates a cohort of GNPs that do not leave the EGL GZ in mouse models of Shh medulloblastoma.…”
Section: Relevance To Other Models and To Neurodevelopmental Diseasesupporting
confidence: 83%
“…Recent studies have expanded our knowledge of the role of the Pard complex in mediating key integrative steps in the response of GNPs and CGNs to niche conditions to organize cell biological pathways responsible for differentiation. Ong et al (2020) used sophisticated imaging technologies to reveal how the Pard complex participates in a coincidence detection circuit between the pial ECM and Shh signaling at the level of GNP ciliogenesis ( Figure 1 ). Pioneering studies by Mueller and colleagues showed that Shh signaling required beta 1 integrin receptors to modulate GNP proliferation effectively; however, the mechanism by which this occurred was unclear ( Blaess et al, 2004 ).…”
Section: Cell Polarity and The Intrinsic Machinery That Interprets Ge...mentioning
confidence: 99%
See 1 more Smart Citation